IMPLEMENTING PROBLEM BASED LEARNING INTEGRATED WITH COOPERATIVE LEARNING TEAMS GAMES TOURNAMENT IN IMPROVING STUDENTS’ ACHIEVEMENT IN TEACHING COLLOIDAL SYSTEM - Anggun C. Pardosi; Wesly Hutabarat (JURNAL PENELITIAN BIDANG PENDIDIKAN, 2015)
Abstract The research was conducted on grade 11 of SMA Negeri 15 Medan,North Sumatera. The effect of problem based learning integrated with cooperativelearning teams games tournament on students’ achievement was investigated inorder to know the significance difference between students’ achievement in 1thexperimental class and 2experimental class using problem based learning model.The populations were all of the students in grade 11nd  SMA Negeri 15 Medan andsamples selected by purposive random sampling techniques. As many as 20validated multiple choice questions used to measure students’ achievement andobservation sheet used to measure lesson materials. Pretest used to determinestudent background knowledge. Afterward, teaching treatment was carried outtoward both 1st experimental and 2ndth experimental classes. The last step is to carryout posttest for both of the classes. Data collected were analyzed by SPSS -17 forwindows. Results showed that there was a positive effect of problem based learningmodel integrated with cooperative learning teams games tournament on students’achievement.  stKeywords:Problem BasedLearning Model,Teams Games Tournament, Student’sAchievement.